FEATURES FORMALIZATION TASKS OF FORMATION OF SOLUTIONS FOR FUNCTIONAL AND PRODUCTION MANAGEMENT INDUSTRIAL ENTERPRISES IN THE MARKET - S. Logvinov (Вестник университета)
The article deals with issues related to the characteristics of the formalization of tasks of forming solutions for functional and production management of industrial enterprises in market conditions. Particular attention is paid to the economic and mathematical modeling of structural and manufacturing processes in industrial plants.